KECELAKAAN KERJA DALAM KEGIATAN EKSPLOITASI HUTAN DI KALIMANTAN TENGAH - Maman Mansyur Idris; Soenarno Soenarno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
Logging in Central Kalimantan is generally mechanized, utilizing modern machines. Involved in these activities are local labourers, many among which have not benefited any adequate training for their jobs. They are originally farmers or farm labourers, and most of them had very little, if any education. It is therefore, not surprising that they can't operate or handle the machines properly.The logging industry is characterized by hard work requiring, high skill and alertness.Shortcomings in these qualities leads to accidents caused by inumerable factors that are constantly present in the tropical high forests. To develop safety programs research is needed to gather information on work accidents at various logging companies through the years. The aim of this study is to find out about the effects of mechanized logging systems on accident occurrences. The study was conducted in Central Kalimantan, resulting in the following conclusions :1. Accident frequency rate according to ANSI standard for 500 labourers ranges from 95 to 151 accident per million work hours.2. Accident severity rate according to ANSI standard for 500 labourers ranges from 4, 000 to 8, 000 days lost per million work hours